Consistent estimator in multivariate errors-in-variables model in the case of unknown error covariance structure - Kukush, A. G.; Polekha, M. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We consider a linear multivariate errors-in-variables model AX ? B, where the matrices A and B are observed with errors and the matrix parameter X is to be estimated. In the case of lack of information about the error covariance structure, we propose an estimator that converges in probability to X as the number of rows in A tends to infinity. Sufficient conditions for this convergence and for the asymptotic normality of the estimator are found.